Aspirin moderates the association between cardiovascular risk, brain white matter hyperintensity total lesion volume and processing speed in normal ageing. (March 2020) - Khezrian, Mina; Waymont, Jennifer M.J.; Myint, Phyo K.; McNeil, Christopher J.; Whalley, Lawrence J.; Staff, Roger; Murray, Alison D.
Highlights: The role of white matter hyperintensity on cognition in older adults with cardiovascular risk varied by aspirin use. Aspirin use exacerbated the negative effect of white matter hyperintensity burden on cognition. The underlying pathways to cognitive decline may differ among aspirin users. Considering aspirin use in addition to white matter hyperintensity and cardiovascular risk could improve the prediction of cognition in older adults. Abstract: Objectives: Cardiovascular risk is associated with cognitive decline and this effect is attributed to brain pathology, including white matter hyperintensity (WMH) burden. Low-dose aspirin is frequently recommended for reducing vascular events. We investigated the effect of taking aspirin on the association between cardiovascular risk, WMH burden and cognitive function. Study design: The study sample was drawn from 318 dementia-free adults aged 67–71 years. Brain magnetic resonance imaging (MRI) scans were acquired from 239 participants. Main outcome measures: WMH total lesion volumes (TLV) were extracted using the automated lesion segmentation algorithm. We measured cardiovascular risk by calculating ASSIGN score. Cognitive ability was measured using a test of processing speed. We developed structural equation models to test our hypothesis. Results: Sixty-eight participants (47.1 % male, mean age = 68.8 years) reported that they took aspirin. The demographic measures did not differ significantly by aspirin use. Among aspirin users, there was a strong negative association between WMH TLV and cognition (β = −0.43, p-value < 0.001), while in non-users of aspirin the only significant predictor of poorer cognition was cardiovascular risk (β = −0.17, p-value = 0.001). Conclusions: Aspirin use moderates the negative effect of WMH burden on cognition. Considering WMH burden in addition to cardiovascular risk could improve the prediction of cognitive decline in older adults with aspirin use.